Urgensi Komisi Perlindungan Anak Daerah (KPAD) Kabupaten Asahan dalam Memberikan Perlindungan Hukum Anak - Ari Dermawan; Riswan Munthe; Rahmat Hidayah (DOKTRINA: JOURNAL OF LAW, 2021)
The Regional Child Protection Commission (KPAD) of Asahan Regency is an institution that is the party in providing protection for children from various kinds of crimes, both children become victims and children are perpetrators. The purpose of this research is to discuss the legal basis for implementing the Regional Child Protection Commission (KPAD) of Asahan Regency, and the implementation of legal protection for children by the Regional Child Protection Commission (KPAD) of Asahan Regency. The research method used is empirical legal research by analyzing primary data and secondary data by examining directly into the field and both from literature.Based on the results of this study, that the basis of legal regulation regarding child protection is Law Number 35 of 2014 concerning Child Protection. The Regional Child Protection Commission (KPAD) of Asahan Regency carries out mandatory duties in accordance with existing statutory regulations. The Regional Child Protection Commission (KPAD) of Asahan Regency provides protection for children as victims and actors in a comprehensive (multi-aspect), holistic (comprehensive, integrated) and coordinated integrated service.